Analysis of Internal Communication and Job Satisfaction on Employee Loyalty and Service Quality at Import Companies in Jakarta - Mohamad Fresal Sugeha; Hendi Budiman; Eva Yuniarti Utami; Aan Adiazmil (Jurnal Multidisiplin West Science, 2024)
This study investigates the relationship between internal communication, job satisfaction, employee loyalty, and service quality in a Jakarta-based import company. Through quantitative analysis involving 150 employees, this study used Structural Equation Modeling (SEM-PLS) to examine the relationships among these key variables. The findings show a significant positive relationship, indicating that effective internal communication and increased job satisfaction positively influence service quality and employee loyalty. The results of this study carry implications for organizational strategies in fostering a conducive work environment, increasing employee satisfaction, and ultimately improving service quality in the context of the import industry in Jakarta.